Asset-Based Batik Shibori Mentoring to Foster Rural Children’s Creativity: An ABCD Community Empowerment Model - Arif, Muhamad; Nisa’, Khoirotun; Sakdiyah, Nur Halimatus; Maulidina, Mazilda Nur; Ulilhaq, M.Rifqi Amirul (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
Education plays a crucial role in shaping the quality of human resources, particularly in fostering higher-order thinking skills and children's creativity in the globalization era. Nevertheless, creative development in rural areas remains suboptimal due to limited experiential art-based learning programs. This community service program aimed to assist children's creativity through the practice of shibori tie-dye batik using the Asset Based Community Development (ABCD) approach. The activity was conducted on 22–23 November 2025 in Sembung Village, Wringinanom District, Gresik Regency, involving 27 children as participants. The mentoring stages followed the ABCD framework: define, discover, dream, design, and deliver, focusing on direct introduction and practice of folding, binding, and dyeing textile techniques. Data were collected through observation, documentation, and short interviews to measure creativity improvement indicators such as motif diversity, color combinations, and experimentation courage. The results indicated a significant increase in children's creativity and independence in performing each batik-making stage, along with enhanced character formation in patience, accuracy, responsibility, and social cooperation. Participants expressed sustained interest due to the interactive, enjoyable, and meaningful learning experience. This program is recommended as an effective, culturally-based creative mentoring model that supports children's potential development in rural communities